Evaluasi Penerapan Sistem Informasi Pendaftaran Umum dengan Menggunakan Metode Pieces di RSUD Kabupaten Sidoarjo - Dara Ayu Nirwana; Ervina Rachmawati (Politeknik Negeri Jember, 2020)
The development information technology has a major influence on health services in meeting community'sneed for speed and accuracy of health services provided by hospitals. General registration counters areone place service for visitors who do not use state health insurance or from government as initial sourceservices provided by hospitals. Problems arising from general registration performance aspect is the timerequired while the service is in operation in operating the information system causes loading problems thatresult in the continuation of service.The aspect of general registration information system can not bridge orrun with other application systems such as applications provided by the Sidoarjo District Health Office. Inaspect of system control, differences in access for each user, but officers sometimes still lend users toother officers because each user has different access rights security still not guaranteed. Efficiency andService aspects, where features in general registration information system have made it easier for officersto operate easily but provide new features that must be learned by self-taught officers. As Service, thereare no modules or guidelines for operating a general patient registration information system. Datacollection methods with interview techniques and arragements. Data analysis by drawing conclusions thenanalyzing and giving advice. The purpose of this study to study general registration information system.Type of qualitative research. Respondents used 1 general registration officer. Results of this study notethat Service, Efficiency, Control, Economic, Information and Performance factors are related to use of ageneral registration information system.